Equivariant perturbation in Gomory and Johnson's infinite group problem (V). Software for the continuous and discontinuous 1-row case. (4th May 2018) - Hong, Chun Yu; Köppe, Matthias; Zhou, Yuan
Abstract : We present software for investigations with cut-generating functions in the Gomory–Johnson model and extensions, implemented in the computer algebra system SageMath.